The Importance of Enhancing the Passion of Interest in Reading Students Through Libraries - Fadillah, Maya Nurul (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2020)
This research was carried out aimed at informing that the importance of reading to improve the intelligence of the nation and increase insight or knowledge. The teacher is the main factor that supports in increasing interest in reading students. The method in this study is a qualitative descriptive method. Obtaining data obtained from observations This study was conducted because students' interest in reading was too low. From the results of research that has been investigated the cause of low student interest is because students assume reading books is boring and saturating. Therefore this study was conducted so that teachers better understand their students that reading is very important and add insight and knowledge and the teacher must make a way like the teacher must talk to the principal to add comics to the library so that when students librarians don't just textbooks that he met but there were comics, fairytale books, folklore books, etc.